Nekaj shematičnih misli ob zborniku Kakšna sociologija? Za kakšno družbo? - Močnik, Rastko (Teorija in praksa, 2018)
Reading Professor Zdravko Mlinar's anthology, the article contends that four sociological problematics have so far been developed in Slovenia: Marxist, empirical, radical theoretical problematics and integrated social science. The article hypothesises that these problematics can be linked to world-historical ruptures during the last 50 years, and to the major periods of Yugoslav socialism. The text proposes the thesis that the empirical problematics have failed to confront the restoration of capitalism. Rather, they have transformed into predominantly ideological "studies" that prevent integrated social science from developing within academic and research institutions.
Keywords: Epistemologija družbenih ved; Epistemology of the social sciences; Sociological orientation; Sociologija; Sociology; Sociološke smeri